2022
DOI: 10.1101/2022.02.06.479300
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aging clocks, entropy, and the limits of age-reversal

Abstract: We analyze aging signatures in the DNA-methylation and Electronic Medical Records from the UK Biobank datasets and observe that aging is driven by a large number of individually rare and independent transitions between metastable states in a vast configuration space. The compound effect of the configuration changes can be captured by a single stochastic variable, the thermodynamic biological age (tBA), tracking the entropy produced and hence the information lost in the aging process. We show that tBA increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 74 publications
3
24
0
Order By: Relevance
“…1h ), thus resembling exponential-decay-like changes in the average methylation levels within the defined dynamics of DNAm changes. This is consistent with the aging-related increase in entropy metrics based on various molecular and functional readouts 12,3134 .…”
Section: Resultssupporting
confidence: 85%
“…1h ), thus resembling exponential-decay-like changes in the average methylation levels within the defined dynamics of DNAm changes. This is consistent with the aging-related increase in entropy metrics based on various molecular and functional readouts 12,3134 .…”
Section: Resultssupporting
confidence: 85%
“…Previous studies found an accelerated increase in DNA methylation Shannon entropy with adult age 21,33,34 , which is in line with the notion of accumulation of age-related damage. Using skin and embryo DNA methylation data, we examined the dynamics of methylation entropy in the frog.…”
Section: Profiling Dna Methylation During Aging and Embryonic Develop...supporting
confidence: 86%
“…The benefit may be particularly huge in studies involving large sets of longitudinal measurements but often lacking follow-up mortality and morbidity information. While hallmarks of aging in mice are correlated and primarily reversible, a large part of physiological changes associated with aging in humans is stochastic and may be thermodynamically irreversible 62 . Therefore, we expect that the systematic application of dynamic systems theory principles to biomedical data analysis will help identify actionable aging phenotypes and thus facilitate the discovery and development of anti-aging therapeutics that produce lasting rejuvenating effects.…”
Section: Discussionmentioning
confidence: 99%